2018
DOI: 10.3389/fnins.2018.00051
|View full text |Cite
|
Sign up to set email alerts
|

Homer1a Attenuates Hydrogen Peroxide-Induced Oxidative Damage in HT-22 Cells through AMPK-Dependent Autophagy

Abstract: Neuronal oxidative stress is involved in diverse neurological disorders. Homer1a, as an important member of the Homer family and localized at the postsynaptic density, is known to protect cells against oxidative injury. However, the exact neuroprotective mechanism of Homer1a has not been fully elucidated. Here, we found that Homer1a promoted cell viability and reduced H2O2-induced LDH release. The overexpression of Homer1a enhanced autophagy after H2O2 treatment, which was confirmed by increased expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
(33 reference statements)
5
9
0
Order By: Relevance
“…We therefore made an assumption that TLB controls mtROS homeostasis via activating the AMPK-PGC-1α- Sirt3 axis. As expected, the results indicated that H 2 O 2 decreased p-AMPK, in keeping with the theory that oxidative stress acts as a trigger for AMPK (Wu et al, 2018 ). Whereas, TLB promoted AMPK phosphorylation, thereby triggered activation of PGC-1α and ERRα, suggesting that AMPK-PGC-1α-Sirt3 axis was necessary for the protective effect of TLB on regulation of mtROS homeostasis in neuronal cells.…”
Section: Discussionsupporting
confidence: 90%
“…We therefore made an assumption that TLB controls mtROS homeostasis via activating the AMPK-PGC-1α- Sirt3 axis. As expected, the results indicated that H 2 O 2 decreased p-AMPK, in keeping with the theory that oxidative stress acts as a trigger for AMPK (Wu et al, 2018 ). Whereas, TLB promoted AMPK phosphorylation, thereby triggered activation of PGC-1α and ERRα, suggesting that AMPK-PGC-1α-Sirt3 axis was necessary for the protective effect of TLB on regulation of mtROS homeostasis in neuronal cells.…”
Section: Discussionsupporting
confidence: 90%
“…However, accumulation of excess ROS is a potent inducer of dysfunction in CNS, which results in oxidative damage and various neurodegenerative disorders. Chronically elevated levels of H 2 O 2 have been implicated in cell viability in multiple neuronal cells [23, 24]. To determine the H 2 O 2 toxicity on neural cells, alamarBlue reagent was used to assess cell viability.…”
Section: Resultsmentioning
confidence: 99%
“…Generation of intracellular ROS following H 2 O 2 treatment is known to contribute to oxidative stress [ 36 , 37 , 38 ]. To confirm that H 2 O 2 treatment leads to ROS generation and to further understand the modulation of the H 2 O 2 -induced oxidative stress by STING in this study, intracellular ROS levels in H 2 O 2 treated WT and STING −/− cells were measured by a 2′, 7′-dichlorofluorescin (DCF) assay.…”
Section: Resultsmentioning
confidence: 99%
“…These discrepancies observed underscore our lack of understanding of how STING modulates autophagic activity in different disease models. Evidence in the literature has also associated H 2 O 2 -induced oxidative stress with autophagy activation [ 26 , 36 ]. It is possible, therefore, that STING may act as a molecular switch in promoting either detrimental or beneficial outcomes in TBI and H 2 O 2 -induced oxidative stress, respectively, by modulating autophagy activity.…”
Section: Discussionmentioning
confidence: 99%